Effects of Psaltery Cassava Out-grower Scheme in Enhancing Smallholder Productivity and Sustainable Livelihood in South-West Region Nigeria - Oladimeji Ibrahim Alarape (Fakultas Ekonomi, Universitas Bangka Belitung, 2021)
Cassava value addition efforts suffer a serious setback in Nigeria despite huge production potentials due to a weak linkage between producers and processors. Psaltry cassava out-grower scheme thus emerged as a model to facilitate the needed linkage and boost farmers' productivity. The need to understand how the Psaltry model has encouraged increased cassava productivity informed this study on the effects of Psaltry cassava out-grower scheme in enhancing smallholder productivity in the Oyo State, Nigeria. Pre and post-intervention combined with treatment and control group designs were used for the study. Simple random sampling was used to elicit information from 280 out-growers and 49 non-out-growers using interview schedules on their socio-economic characteristics, supports received from Psaltry, perception of Psaltry, change in cassava productivity due to participation in the Psaltry scheme and challenges faced in the scheme. Data were analysed using descriptive statistics and regression analysis at α 0.05. Out-growers were aged 46.5±17.3 years, had 2.8±1.1 years of experience with Psaltry, mostly (65.9%) male, belonged to farmers group (96.1%) and had at least primary school education (60.8%). Assured markets (90.5%) and training on post-harvest handling of crops (69.9%) were most common supports received from Psaltry. More than half (56%) of out-growers had favourable perception of the Psaltry scheme as unclear procedures (2.23±0.7) ranked as the most severe constraint faced in the scheme. Total cassava harvested and productivity among out-growers increased from 30,950.89±31,133.48kg to 106,116.88±96,926.01kg and 5,474.05±3,881.05kg/Acre to 9,126.51±8,783.89kg/Acre before and after participating in Psaltry scheme, respectively. Productivity was found to be higher among out-growers (9,126.51±8,783.89kg/Acre) than non-out-growers (1,047.24±4,789.34kg/Acre). Membership of group (β=0.319) and length of involvement in Psaltry scheme (β=0.157) positively and significantly influenced out-growers change in cassava productivity. Psaltry out-grower scheme had stimulated beneficiary’s smallholder farmers towards higher productivity through assured markets for their cassava zproduce. Also, farmers increased income as enhanced better sustainable livelihood which theyr have be able to expand their capabilities and assets. A scale-up of the Psaltry model has prospects for transforming smallholder farmers to commercial producers. Keywords: Out-grower scheme, Cassava farmers, Market linkage, Smallholder farmer, Psaltry.